Communicating COVID-19 risk changes: Signalling with words, phrases, and messages. (July 2022) - Mehta, Amisha M.; Murray, Scott; Weeks, Clinton S.
Abstract: During COVID-19, governments issued messages to trigger action, encourage sustained behaviours (e.g., social distancing, hand hygiene), and manage system wide risk. This study examines messages issued across two stages established by the World Health Organization (WHO): (a) pre-pandemic early intervention stage and (b) within-pandemic escalation stage. In April 2020, approximately one month after COVID-19 was declared a pandemic, an experiment using a sample of 769 Australian participants was conducted. Using a between-subject design, participants assessed the way messages (curated and then expertly attributed to the two stages) were perceived and influenced behaviours. Next, it examined the power of words and phrases, selected from the same messages, for (a) their potential to signal risk, warning, and behavioural response and (b) the extent to which they reflected pandemic stages. Results showed that between the two stages, messages were differentiated by negative affect, assertiveness, and risk. Subsequently, increased negative affect, assertiveness, and risk indication increased adaptive behavioural intentions. However, increased assertiveness also increased non-adaptive behavioural intentions, though increased risk indication reduced non-adaptive behavioural intentions. Signal words and phrases, which hold potential as iconic features for biological hazard messages, showed varying performance across message stages, indicating an opportunity to improve them. Taken together, the findings contribute to academic and policy approaches for adapting communication to changing risk.